Karakter pintu masuk sarang kelulut (Apidae: Meliponinae) di Kawasan Konservasi Resort Belaban Taman Nasional Bukit Baka Bukit Raya Kalimantan Barat: Nest entrances characters of stingless bees (Apidae: Meliponinae) in Conservation Area of Belaban Resort, Bukit Baka Bukit Raya National Park West Borneo - Rivaldy, Marsianus Marthin; Kustiati, Kustiati; Rousdy, Diah Wulandari; Priyandono, Hendro (Jurnal Entomologi Indonesia, 2023)
Information on the character of the stingless bee nest entrance (Hymenoptera: Apidae: Meliponinae) as a characteristic for identifying stingless bee species has never been carried out in depth. The purpose of this study was to determine the morphological characteristics of the nest entrance that differentiate between stingless bee species found in the Belaban Resort conservation area, Bukit Baka Bukit Raya National Park. The research was conducted on March, 16–26 2022. The method used in this study was the cruising method by following the direction of the Belaban Resort interpretation route. Data analysis was performed with PAST 4.03 software. Based on sampling and species identification, 32 nest entrances were found from 7 stingless bees species, namely Homotrigona fimbriata (Smith), Pariotrigona pendleburyi (Schwarz), Tetragonilla collina (Smith), Tetragonula iridipennis Smith, T. melanocephala (Gribodo), T. melina (Gribodo), and Tetrigona apicalis (Smith). PCA results show that the most prominent morphometric characters in PC 1 (eigenvalue = 4.89; % variance = 44.51%) which can be used as identifiers for each stingless bee nest entrance width of the nest entrance opening cavity  (0.66), color (0.78), sun exposure (0.85), and shape of nest entrance funnel (0.57). This research shows the variation of meristic and morphometric characters of stingless bee nest entrance. However, identification for stingless bee species based on nest entrance characters can't be used validly so it only as a provisional estimate.